2013
DOI: 10.1021/ol4022639
|View full text |Cite
|
Sign up to set email alerts
|

Myristicyclins A and B: Antimalarial Procyanidins from Horsfieldia spicata from Papua New Guinea

Abstract: An antimalarial screen for plants collected from Papua New Guinea identified an extract of Horsfieldia spicata as having activity. Isolation of the active constituents led to the identification of two new compounds: myristicyclins A (1) and B (2). Both compounds are procyanidin-like congeners of myristinins lacking a pendant aromatic ring. Myristicyclin A was found to inhibit the ring, trophozoite, and schizont stages of Plasmodium falciparum at similar concentrations in the mid-μM range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…[9] In our specific example, the substitution pattern of the benzene ring of the putative chromone is identical to that of the coisolated 9. [13] Instead, the presence of a methyl group in our metabolites makes our carbon skeleton unique and is also consistent with the fact that filamentous fungus produce no flavonoid-related compounds. [10] The biosynthetic route to sancti derivatives might rely on the oxidation of the chromene to the corresponding ortho-quinone methide.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…[9] In our specific example, the substitution pattern of the benzene ring of the putative chromone is identical to that of the coisolated 9. [13] Instead, the presence of a methyl group in our metabolites makes our carbon skeleton unique and is also consistent with the fact that filamentous fungus produce no flavonoid-related compounds. [10] The biosynthetic route to sancti derivatives might rely on the oxidation of the chromene to the corresponding ortho-quinone methide.…”
Section: Resultssupporting
confidence: 78%
“…The comparison of the 13 C NMR spectra of 3 and 1 revealed that the chemical structure of the former was highly similar to that of the latter with an addition of thirteen carbon atoms (Table 1). In an attempt to discriminate between the possible diastereoisomers, 13 C NMR modeling of the eight possible structures was performed through the well-established calculation of the DP4 probability. The four remaining carbon atoms corresponded to one methine group (δ H = 3.93 ppm; δ C = 30.9 ppm, C-7′), one olefinic methine group (δ H = 4.48 ppm; δ C = 100.7 ppm, C-8′), one oxygenated quaternary olefinic carbon atom (δ C = 149.1 ppm, C-9′), and one methyl group (δ H = 1.85 ppm; δ C = 19.0 ppm, C-10′).…”
Section: Resultsmentioning
confidence: 99%
“…From the database searches, 830 (“malaria and flavonoids”: 540; “Chagas disease and flavonoids”: 60; “leishmaniasis and flavonoids”: 124; “dengue and flavonoids”: 106) potentially relevant records were identified, from which 737 were excluded after screening the titles or abstracts. The full reports of 93 articles were acquired: 83 studies related to natural flavonoids (Adinehbeigi, Razi Jalali, Shahriari, & Bahrami, ; Allard et al, ; Anusuya & Gromiha, ; Anusuya & Gromiha, ; Assis et al, ; Azebaze et al, ; Beer et al, ; Cabanillas et al, ; Castro, Barrios, Chinchilla, & Guerrero, ; Cheema et al, ; Cornelio et al, ; Coulerie et al, ; Cunha‐Rodrigues et al, ; Da Rocha et al, ; Da Silva, Maquiaveli, & Magalhães, ; De Monbrison et al, ; De Sousa et al, ; De Sousa et al, ; Dos Reis, Manjolin, Maquiaveli, Santos‐Filho, & da Silva, ; Ezenyi et al, ; Fonseca‐Silva, Inacio, Canto‐Cavalheiro, & Almeida‐Amaral, ; Fonseca‐Silva, Inacio, Canto‐Cavalheiro, Menna‐Barreto, & Almeida‐Amaral, ; Frabasile et al, ; Freitas et al, ; Ganesh et al, ; Gontijo et al, ; Grael, Albuquerque, & Lopes, ; Grecco et al, ; Güida et al, ; Heh et al, ; Houël et al, ; Ichino et al, ; Ijaz, Ahmad, Ahmad, ul Haq, & Wang, ; Inacio, Gervazoni, Canto‐Cavalheiro, & Almeida‐Amaral, ; Ismail & Jusoh, ; Jasmeen et al, ; Jin et al, ; Kapingu et al, ; Kiat et al, ; Kimmel et al, ; Konziase, ; Kraft et al, ; Kraft et al, ; Lage et al, ; Lage et al, ; Lehane & Saliba, ; Leite et al, ; Lu et al, ; Manjolin, dos Reis, Maquiaveli, Santos‐Filho, & da Silva, ; Marín et al, ; Marín et al, ; Mittra et al, ; Moghaddam et al, ; Montenegro, Gonzalez, Ortega‐Barria, & Luis Cubi...…”
Section: Methodsmentioning
confidence: 99%
“…After 72 hr of incubation, glabridin ( 15 ) showed antimalarial activity against P. falciparum NF‐54 with IC 50 value of 23.9 μM, with selectivity to Vero cells (SI: 9.6; Cheema et al, ). Two procyanidins myristicyclin A ( 16 ; IC 50 : 35, 43, and 54 μM, respectively) and B ( 17 ; IC 50 : 10.0, 6.6, and 7.9 μM, respectively; [SI: 23.00, 34.84, and 29.11, respectively; red blood cells]) exhibited poor to moderate antimalarial activity against ring, trophozoite, and schizont stages of P. falciparum (Lu et al, ). Four isoflav‐3‐enes [burttinol‐A ( 18 ), burttinol‐B ( 19 ), burttinol‐C ( 20 ), and eryvarin H ( 21 ), and three flavanones [4′‐O‐methylsigmoidin ( 22 ), abyssinone V ( 23 ), and abyssinone V methyl ether ( 24 )] of Erythrina burttii roots inhibited (after 72 hr of incubation) the growth of P. falciparum D6 and W2, with IC 50 values ranging from 4.9 to 13.3 μg/ml and 6.1 to 21.1 μg/ml, respectively.…”
Section: Natural Flavonoids As Potential Leads For the Treatment Of Mmentioning
confidence: 99%
“…Literature survey showed that most phytochemical investigations were focused on the seeds of those species, as the seeds of Horsfieldia glabra, Horsfieldia pandurifolia and Horsfieldia tetratepala are good resources for industrial oil (Xu et al 2012). Previous phytochemical investigation of non-oil constituents on the genus led to the isolation of arylalkanones, lignans, chromones, flavones, alkaloids and steroids, and some of the compounds demonstrated antimalarial and cytotoxic activities Tillekeratne et al 1982;Pinto et al 1988;Jossang et al 1991;Gonzalez et al 2002;Al-Mekhlafi et al 2013;Lu et al 2014). H. pandurifolia is endemic to the subtropical area of Yunnan, China.…”
Section: Introductionmentioning
confidence: 99%